2 - Postcolonial debates in Germany – An Overview - Elise Pape, (African Sociological Review, 2017)
Historiographical works and public thinking in Germany have long considered the German colonial period to be marginal because of its short span – 30 years – compared to other colonial Empires. Throughout the last two decades, various studies have contradicted these ideas and emphasized the impact of German colonization not only on formerly colonialized populations but also on today’s German collective imagination2. In 2004, the centenary year of the Herero and Nama genocide committed in Namibia during German colonization, there was noticeable change in German discussions on the topic. Since then, a renewed interest for postcolonial matters has been observed in public and scientific debates. Several associations have been created in Germany since the mid 2000s with the objective of decolonizing the public space, believing that the process of decolonizing has two sides and cannot only concern formerly colonized states, but also formerly colonizer states3. This article focuses on the main crosscutting themes of German postcolonial debates and the light they can shed on other larger European debates.